The Road to the Beijing Winter Olympics and Beyond: Opinions and Perspectives on Physiology and Innovation in Winter Sport - Wang J; Guan H; Hostrup M; Rowlands DS; González-Alonso J; Jensen J (Springer Nature, 2021)
Beijing will host the 2022 Winter Olympics, and China strengthens research on various aspects to allow their athletes to compete successfully in winter sport. Simultaneously, Government-directed initiatives aim to increase public participation in recreational winter sport. These parallel developments allow research to advance knowledge and understanding of the physiological determinants of performance and health related to winter sport. Winter sport athletes often conduct a substantial amount of training with high volumes of low-to-moderate exercise intensity and lower volumes of high-intensity work. Moreover, much of the training occur at low ambient temperatures and winter sport athletes have high risk of developing asthma or asthma-related conditions, such as exercise-induced bronchoconstriction. The high training volumes require optimal nutrition with increased energy and dietary protein requirement to stimulate muscle protein synthesis response in the post-exercise period. Whether higher protein intake is required in the cold should be investigated. Cross-country skiing is performed mostly in Northern hemisphere with a strong cultural heritage and sporting tradition. It is expected that innovative initiatives on recruitment and training during the next few years will target to enhance performance of Chinese athletes in classical endurance-based winter sport. The innovation potential coupled with resourcing and population may be substantial with the potential for China to become a significant winter sport nation. This paper discusses the physiological aspects of endurance training and performance in winter sport highlighting areas where innovation may advance in athletic performance in cold environments. In addition, to ensure sustainable development of snow sport, a quality ski patrol and rescue system is recommended for the safety of increasing mass participation.
Open Access This article is licensed under a Creative Commons Attri bution 4.0 International License, which permits use, sharing, adapta tion, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article's Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article's Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/
Keywords: Asthma; Cross-country skiing; Endurance training; Exercise physiology; Maximal oxygen uptake; Protein; Ski patrol; Temperature